CircTLK1 Knockdown Alleviates Cell Inflammation and Apoptosis by Regulating Elavl1/Nox4 Axis in Neonatal Sepsis-Induced Lung Injury in Mice - Li, Hongxia; Li, Jiansheng; Zhang, Jin (American Journal of Perinatology, 2024)
Septic acute lung injury (ALI) is a common complication of sepsis with high morbidity and mortality but lacks specific treatment. This study aimed to elucidate the role of circular RNA TLK1 (circTLK1) in neonatal septic ALI.Murine cecal slurry was used to induce neonatal sepsis-induced ALI model in vivo. Hematoxylin and eosin staining was performed to detect the pathological changes in lung tissues. Pulmonary microvascular endothelial cells were treated with lipopolysaccharide (LPS) to induce neonatal sepsis-induced ALI model in vitro. The levels of IL-1β and IL-6 were detected by enzyme-linked immunosorbent assay. A lactate dehydrogenase (LDH) detection kit was used to detect LDH activity. Cell Counting Kit-8 assay and flow cytometry detected cell viability and apoptosis. The genes' expression was measured by quantitative real-time reverse-transcription polymerase chain reaction and western blot. The relationship between circTLK1 and Elavl1 or Elavl1 and Nox4 was detected using RNA immunoprecipitation assay.Our results illustrated that circTLK1 was highly expressed in neonatal sepsis-induced ALI model, and circTLK1 knockdown alleviated cell inflammation and apoptosis in neonatal sepsis-induced ALI model. Similarly, we found that circTLK1 knockdown alleviated neonatal sepsis-induced ALI. Mechanically, circTLK1 mediated Elavl1 binding to Nox4 messenger RNA and increased its stability. Functionally, circTLK1 knockdown alleviated cell inflammation and apoptosis by regulating Nox4 in the neonatal sepsis-induced ALI model.CircTLK1 knockdown alleviated cell inflammation and apoptosis by the Elavl1/Nox4 axis in neonatal sepsis-induced ALI. Our research provided a novel direction for the treatment of neonatal sepsis-induced ALI.
Keywords: circTLK1; septic-induced lung injury; Nox4; inflammation; apoptosis